Symptomatic Signs of Disease of the Lower Joints - Astanov O. M. (Researchparks Publishing, 2022)
A number of domestic and foreign scientific studies on the diagnosis, treatment and prevention of pain syndromes of the temporomandibular joint among the population show that patients with painful joint syndromes or pain syndromes of dysfunction of the joints and disorders in the dentoalveolar system (ZChS) often turn to dentists as the main factors of the pathological process in the body, articulation-occlusion syndromes without changing the structural state of the bone elements, others - hypertonic syndromes of masticatory muscles, the combined effect of various external and internal factors, it was also noted that the violation of the psycho-emotional state is an important etiological factor in the development of dysfunction of the temporomandibular joint [2.4.6.8.12].